Relationship between vocal symptoms in college students and their possible causes - Ferreira, Léslie Piccolotto; Guerra, Juliana Ranzani; Loiola, Camila Miranda; Ghirardi, Ana Carolina de Assis Moura (International Archives of Otorhinolaryngology, 2012)
Introduction: Studies to understand the vocal profile of a population are important to plan collective health measures. The prevalence of vocal symptoms can be indicative of vocal disorder and must be investigated to support measures to prevent vocal diseases.Aim: To characterize vocal symptoms in college students and their possible causes, and to analyze the association between hoarseness, vocal fatigue, phlegm, and burning in the throat with the possible causes mentioned.Method: Prospective study of 517 students who answered a questionnaire about their general heath and vocal symptoms and causes. We used the study of proportions, measures of central tendency, and a chi-square test to associate the presence of symptoms and possible causes.Results: Symptoms most often mentioned: dry mouth (21%), dry throat (18.2%), phlegm (17.9%). Causes most often cited: high respiratory disease (39%), intense voice use (24%), smoking (24%). Hoarseness was associated with heavy use of voice and high respiratory disease; vocal fatigue with intense voice use, stress, and digestive problems; burning in the throat with intensive voice use, high respiratory disease, and pollution; phlegm with smoking, and upper respiratory and digestive problems.Conclusion: Not only do aspects of health and the voice interfere with its production, the external environment and habits influence the vocal symptoms of this population as well.
Keywords: epidemiology; voice; voice disorders; speech, language and hearing sciences